2005
DOI: 10.1111/j.1442-2050.2005.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1, E2F1 expression levels are associated with characteristics and prognosis of esophageal squamous cell carcinoma

Abstract: SUMMARY. We performed a multi-institutional analysis of E2F1 and cyclin D1 expression in cases of esophageal squamous cell carcinoma (ESCC). Cyclin D1 and E2F1 are involved in the transition of cell cycle phases and associated with tumor progression. However, no previous studies have concurrently analyzed combined E2F1 and cyclin D1 expression. The purpose of this study was to clarify the relationship of E2F1 and cyclin D1 in ESCC. We studied 122 patients with primary ESCC who underwent surgical tumor resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…However, most data available focus on the function of proliferation-promoting E2F transcription factors, in particular E2F1, in malignant cells. [11][12][13][14][15][16][17] In fact, in non small lung cell carcinoma and esophageal squamous cell carcinoma upregulation of E2F1 was associated with growth advantage and poor clinical outcome. [11][12][13] In small lung cell carcinoma overexpression of E2F1 was linked to deregulation at the transcriptional level, rather than to gene amplification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most data available focus on the function of proliferation-promoting E2F transcription factors, in particular E2F1, in malignant cells. [11][12][13][14][15][16][17] In fact, in non small lung cell carcinoma and esophageal squamous cell carcinoma upregulation of E2F1 was associated with growth advantage and poor clinical outcome. [11][12][13] In small lung cell carcinoma overexpression of E2F1 was linked to deregulation at the transcriptional level, rather than to gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] In fact, in non small lung cell carcinoma and esophageal squamous cell carcinoma upregulation of E2F1 was associated with growth advantage and poor clinical outcome. [11][12][13] In small lung cell carcinoma overexpression of E2F1 was linked to deregulation at the transcriptional level, rather than to gene amplification. 11 Based on the hypothesis that expression levels of E2F transcripts are tissue-specific and functions of distinct E2F transcription factors could vary among cell types, 5 this study investigated the whole set of E2Fs in various ovarian cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that cell cycle proteins are critical to regulating cell viability, and cyclin D1 overexpression is significantly associated with poor outcome in esophagus squamous cell carcinoma, 18 we next determined whether S6 or S6K1 affects the expression of cell cycle regulators in G1/S phase transition. Depletion of S6 or S6K1 resulted in a sharp decrease in cyclin D and cdk 2 levels, whereas levels of p21 and p27, which are cyclin-dependent kinase 4/6 inhibitors, were increased, indicating that both S6 and S6K1 regulate cell cycle progression of TE8 and TE10 esophageal cancer cells (Figure 3b and Supplementary Figure S2b).…”
Section: Depletion Of S6 or S6k1 Attenuates Viability Of Esophageal Cmentioning
confidence: 99%
“…In ESCC cells overexpressing active Notch1, we observed down-regulation of cyclin D1, cyclin E and CDK2, which were considered to be correlated with the altered cell cycle distribution phenotype and growth suppression, also, cell numbers at G 0 /G 1 phase in EC9706 cells transfected with pcNICD markedly increased compared to that in EC9706 cells untreated or transfected with pcDNA3.1, suggesting the proliferation of ESCC cells was suppressed due to the expression changes of cell cycle protein, cyclin D1, cyclin E and CDK2. In human ESCC tissues, increased expression level of cyclin D1 speeded the progress of ESCC and led to poor prognosis (32). It has been reported that overexpression of cyclin E was a general phenomenon associated with oncogenesis of breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%